2017
DOI: 10.1073/pnas.1706070114
|View full text |Cite|
|
Sign up to set email alerts
|

Human genetic variation in VAC14 regulates Salmonella invasion and typhoid fever through modulation of cholesterol

Abstract: Risk, severity, and outcome of infection depend on the interplay of pathogen virulence and host susceptibility. Systematic identification of genetic susceptibility to infection is being undertaken through genome-wide association studies, but how to expeditiously move from genetic differences to functional mechanisms is unclear. Here, we use genetic association of molecular, cellular, and human disease traits and experimental validation to demonstrate that genetic variation affects expression of VAC14, a phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 109 publications
(100 reference statements)
0
55
0
Order By: Relevance
“…Examination of SPI-1’s role in SarA translocation is more complex due to the requirement of SPI-1 for entry into non-phagocytic cells (Collazo and Galan, 1997), including LCLs (Alvarez et al, 2017). Therefore, we utilized S. Typhi (which does not contain SarA and therefore does not induce IL-10) to trigger macropinocytosis in the LCLs and co-infected with S .…”
Section: Resultsmentioning
confidence: 99%
“…Examination of SPI-1’s role in SarA translocation is more complex due to the requirement of SPI-1 for entry into non-phagocytic cells (Collazo and Galan, 1997), including LCLs (Alvarez et al, 2017). Therefore, we utilized S. Typhi (which does not contain SarA and therefore does not induce IL-10) to trigger macropinocytosis in the LCLs and co-infected with S .…”
Section: Resultsmentioning
confidence: 99%
“…We reasoned that functional annotations might provide clues to further putatively causal variants among our list of most associated regions. To assess this, we annotated all imputed variants with information indicative of functional importance, including location and predicted function within genes 26 , chromatin state 27–29 and transcriptional activity 28,30,31 across cell types, status as an eQTL 3133 , and association evidence from other traits 3437 . This analysis revealed a number of potentially functional variants with evidence of association ( Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, effects of the proteins sopB and sopE are necessary for Salmonella to induce its own entrance. 27 We have reported that, similar to epithelial cell infection, Salmonella Typhimurium promotes its own entry into spleen mouse B cells in a process dependent on SPI-1 genes. 24 It has also been shown that this entry process can be mediated by the BCR.…”
Section: Spi-5 Encodes a Series Of Proteins Responsible For Enteropatmentioning
confidence: 98%
“…It is well established that B cells are targets of Salmonella infection. [22][23][24][25][26][27][28] In murine models, we observed that Salmonella…”
Section: Spi-5 Encodes a Series Of Proteins Responsible For Enteropatmentioning
confidence: 99%